Sustainable and Scalable Approach for Enhancing the Electrochemical Performance of Molybdenum Disulfide (MoS2). (31st December 2022) - Kumar, Sunil; Kumar, Vinay; Devi, Raman; Sisodia, Avnish Kumar; Jatrana, Anushree; Singh, Raj Bahadur; Dahiya, Rita; Mishra, Ajay Kumar
Abstract : Molybdenum disulfide (MoS2 ), the second most thoroughly investigated two-dimensional material after graphene, has attracted considerable interest in energy storage applications owing to its exceptional qualities, including its unique crystal structure, low electronegativity, and high specific capacity. In this study, we showed that a simple ball-milling procedure causes significant improvement in the capacitive properties of the bulk MoS2 (BL-MoS2 ). We characterized the material before and after the milling process using X-ray diffraction (XRD) and a BET surface area analyzer to find the material's structural, crystalline features, and surface area, respectively. We prepared electrodes of BL-MoS2 and ball-milled MoS2 (BM-MoS2 ) for electrochemical investigation. The charge storage characteristics were examined using cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), and electrochemical impedance spectroscopy (EIS). The BM-MoS2 and BL-MoS2 have a specific capacitance of 114 F/g and 96 F/g, respectively.